Improved Thermal Stability of Silica Nanofluids Using Anionic Surfactants for Enhanced Oil Recovery Applications - Khasan Rowi; Ngadiwiyana Ngadiwiyana; Agus Subagio (Jurnal Kimia Sains dan Aplikasi, 2025)
Silica nanoparticles have shown great potential in the oil and gas industry sector, especially in applications for enhanced oil recovery. Silica nanofluids are widely used in EOR applications because they are inexpensive, easy to synthesize, environmentally friendly, can be surface modified, and provide high oil recovery rates. However, silica nanofluids have drawbacks in thermal stability and salinity at high temperatures, adversely affecting their application in oil reservoirs. In this paper, the effects of a surfactant sulfonate compound (SPU11) and a co-surfactant sulfosuccinate compound (SPU22) on the thermal stability of silica nanofluids at temperatures ranging from 60 to 100°C were investigated. Next, the silica nanofluids were analyzed for particle size using a particle size analyzer (PSA), wettability using a sessile drop contact angle, and oil recovery capacity using a core flooding test. The results showed that the silica nanofluid with 0.3% SPU11 and 0.3% SPU22 surfactant showed good thermal stability below 80°C for 3 months in 3 wt% brine; PSA analysis showed that the aggregate diameter was 52.86 nm; wettability analysis showed that the silica nanofluid had a contact angle of 60.8° to 36.6° and the core flooding results of silica nanofluid showed an oil in place recovery (OOIP) of 9.7%.